Recent Advances in Pancreatitis - Yan, Qiang (IntechOpen, 2022)
Pancreatitis is a common disease of the digestive system with a high mortality and complication rate. This book provides a comprehensive discussion of the anatomy and physiology of the pancreas, acute and chronic pancreatitis, and minimally invasive treatment in pancreatitis. The target audience comprises scholars and specialists in the field.